Political Economy of Regional Integration in Sub-Saharan Africa - Brenton, Paul; Hoffman, Barak (World Bank, Washington, DC, 2016)
Regional integration in sub-Saharan Africa (SSA) is crucial for its further economic development and, more importantly, its structural transformation away from agriculture towards higher value-added activities, such as manufacturing and services. Yet there are many paths towards greater integration, some of which are easier than others. In order to gain insights into how regional integration is occurring in SSA, determine impediments to it, and develop recommendations for how the World Bank and other development agencies can help further facilitate it, the World Bank commissioned a set of political economy of regional integration studies covering sector analyses of agriculture, financial services, professional services, trade facilitation, and transport. This report summarizes the findings from the sector studies and suggests recommendations for further efforts in these areas by the World Bank and other development agencies. In a comparative context, the findings of the studies suggest cautious optimism for regional integration efforts in sub-Saharan Africa. Economic integration is more likely to succeed when it occurs alongside regional attempts at improving political stability and or developing joint infrastructure.